EFEKTIVITAS PENGGUNAAN LKPD BERMUATAN KECERDASAN KOMPREHENSIF BERBASIS MODEL PBL PADA PEMBELAJARAN FISIKA - Ulfa Septi M; M. Rahmad M. Rahmad; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Education is needed to create a characterable and intlligent generation who able to develop their potentials independently. The use of teaching materials in the form of LKPD on the learning process can realize the meaning of education. LKPD is demanded by 2013 Curriculum lesson charges comprehensif intelligence which contains spiritual, emotional-social, intellectual and skill intelligence. Comprehensive intelligence LKPD based on PBL model has been developed by previous researchers but has not been tested its effectiveness, so this study aims to describe the effectivity of LKPD and to know the difference of student learning result using LKPD with comprehensive intelligence and unemployed. This type of research was quasi experiment with Intact Group Comparison design which is consisting of two study classes, experiment class and control class. The population of this research was all students of grade 10th MIPA in SMA N 5 Pekanbaru academic year 2017/2018, where class 10th MIPA 6 (experiment class) and class X MIPA 2 (control class) as samples. The data were obtained in the form of competence value of spiritual, emotional-social, intellectual and skill. The instruments used in this study were syllabus, RPP, LKPD charged with comprehensive intelligent based on PBL model, spiritual and emotional-social observation sheets, skill performance sheets, and cognitive tests. The data obtained were analyzed descriptively for the four intelligences and analyzed inferentially only on intellectual intelligence by using hypothesis test on 5% significance level. The results of this study are 1) LKPD charged with comprehensive intelligence based on PBL model is effective for physics learning of grade 10th in SMA Negeri 5 Pekanbaru especially particle dynamics; 2) there is significant difference in student learning outcomes using LKPD charged with comprehensive intelligence based on PBL model with students who do not use the LKPD.Keywords : Comprehensive Intelligence, Competence, Student Worksheet, Problem Based Learning